The Effectiveness of the Phonics Method on Second-Grade Students’ Reading and Writing Literacy Skills - Yusina Wair; Ismail Marzuki (TEKILA: Journal of Language Teaching and Literature, 2026)
Reading and writing literacy is a fundamental foundation for students to understand learning materials, as every aspect of learning requires effective literacy skills. The low reading and writing literacy skills among second-grade students at Muhammadiyah Aimas Elementary School in Sorong Regency is an urgent issue that needs to be addressed. Based on observations, several students experience difficulties in recognizing letters, sounds, and forming words, which hampers their learning process. This study aims to determine the effectiveness of the phonics method in improving the reading and writing literacy skills of students. The method used is a pre-experimental design without a control group, specifically the One Group Pretest-Posttest Design. The study sample consists of 22 students. The independent variable in this research is the phonics method, while the dependent variable is the students' reading and writing literacy skills. Data were collected using tests and questionnaires. The results indicate a significant increase in the average scores of students, from 57.09 (pretest) to 76.09 (posttest), with a significance level of 0.001. This improvement suggests that the phonics method is effective in helping students understand the relationship between letters and sounds, thereby facilitating their ability to read and write correctly. Additionally, students became more active and enthusiastic during the learning process. These findings align with previous research indicating that the phonics method is an effective instructional strategy for enhancing basic literacy skills in early elementary students.